(untitled) (Current Horticulture, 2024)
The experiment involved the green synthesis of silver nanoparticles (AgNPs) from pomegranate (Punica granatum L.) peel extract to enhance the vase-life of cut carnation (Dianthus caryophyllus L.) flowers. Biosynthesized pomegranate peel extract (PPE)-AgNPs were characterized by UV-visible spectroscopy, fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The intensity of peak at 378 nm in UV-vis spectra, attributed to the surface plasmon resonance of PPE-AgNPs, changes with reaction parameters. The SEM showed cubical shaped nanoparticles with an average particle size of 1 - 3 nm. The 15 mg/l PPE-AgNPs, treatment produced longest vase-life (11 days), while the control resulted in the shortest vase-life (7 days) of cut carnation flowers. Thus, these was positive role of PPE-AgNPs in increasing the vase-life of cut carnation flowers.